2010
DOI: 10.1016/j.jsat.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Male methamphetamine-user inmates in prison treatment: During-treatment outcomes

Abstract: Psychosocial functioning and criminal thinking of methamphetamine-using inmates were examined before and after their completion of primary treatment in three in-prison drug treatment programs (one “outpatient” and two different modified TCs). The sample consisted of 2,026 adult male inmates in 30 programs in Indiana. Data included background, psychosocial functioning, criminal thinking, and therapeutic engagement indicators. Multi-level repeated measures analysis was used to evaluate changes during treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 24 publications
(36 reference statements)
0
23
0
1
Order By: Relevance
“…For during-treatment information, these CEST scales can be expanded to include indicators of therapeutic engagement (Joe, Broome, Rowan-Szal, & Simpson, 2002). While original development and testing of the CEST scales were carried out in community-based treatment settings, they subsequently have been modified for a wide range of applications for CJ-involved drug users (e.g., Garner, Knight, Flynn, Morey, & Simpson, 2007; Joe, Rowan-Szal, Greener, Simpson, & Vance, 2010), including international settings (Simpson et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…For during-treatment information, these CEST scales can be expanded to include indicators of therapeutic engagement (Joe, Broome, Rowan-Szal, & Simpson, 2002). While original development and testing of the CEST scales were carried out in community-based treatment settings, they subsequently have been modified for a wide range of applications for CJ-involved drug users (e.g., Garner, Knight, Flynn, Morey, & Simpson, 2007; Joe, Rowan-Szal, Greener, Simpson, & Vance, 2010), including international settings (Simpson et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A study by Joe, Rowan-Szal, Greener, Simpson, and Vance (2010) assessing the efficacy of in-prison treatment for male methamphetamine abusers demonstrated that criminal thinking predicts treatment engagement better than other variables, including psychosocial functioning. Likewise, Taxman, Rhodes, and Dumenci (2011) studied the criminal thinking patterns of drug-using probationers and found that those with higher levels of criminal thinking were less likely to engage in treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Year of publication: Twelve evaluations were published between 1995 and 2005 25–36 and 13 between 2006 and 2015 37–49 …”
Section: Resultsmentioning
confidence: 99%
“…Country of origin: Over half the evaluations were of programs in the United States ( n =15), 25–28,31–34,36,38,39,41,43,45,48 there were two each from Canada 37,46 and Taiwan, 29,47 and one each from Australia, 35 Croatia, 30 Japan, 40 Poland, 49 the United Kingdom (Wales), 44 and South Korea 42 …”
Section: Resultsmentioning
confidence: 99%